PENGARUH IKLAN, KONFORMITAS DAN GAYA HIDUP HEDONIS TERHADAP PERILAKU KONSUMTIF PENGGUNA E-COMMERCE SHOPEE DI KOTA MOJOKERTO - Salma Egita Fitri Subagyo; Jojok Dwiridotjahjono (STEKOM PRESS, 2021)
There are many e-commerce sites that have been present in Indonesia, one of which is Shopee. Shopee is here to provide many attractive offers such as lots of discounts, promos, cashback etc. This can lead to consumptive behavior. This study aims to determine: (1) The effect of advertising on consumptive behavior (2) The effect of conformity on consumptive behavior (3) The influence of a hedonic lifestyle on consumptive behavior in consumptive behavior. The population of this study were users of the e-commerce application Shopee in Mojokerto. In this study using a sample of 100 respondents. The sampling technique is purposive sampling technique with the criteria of women, domicile in Mojokerto, at least 17 years old, have used or purchased goods or services through the Shopee e-commerce application. Data analysis techniques used validity and reliability tests and hypothesis testing using multiple linear regression analysis, t test, f test, and R2 test. The results of this study indicate that advertising has a positive and significant effect on consumptive behavior, conformity has a positive and significant effect on consumptive behavior, the hedonic lifestyle has a positive and significant effect on consumptive behavior, advertising, conformity and hedonic lifestyle together have a positive and significant effect on behavior. consumptiveperilaku konsumtif.